Equine goiter associated with excess dietary iodine - Eroksuz, H; Eroksuz, Y; Ozer, H; Ceribasi, A; Yaman, I; Iihan, N (Comparative Toxicology Lab, 2004)
Natura I occurring goiter cases are described in 2 newborn Arabian foals whose mares were supplemented with excess iodine during the final 24 w of the pregnancy. Six nursing foals and 2 mares were a I so affected clinical with thyroid hypertrophy. At I east 12 times the maximum tolerable level of iodine supplementation was given, as the dais iodine intake for each mare was 299 mg. The prevalence of goiter cases was 2 and 9% in the mares and foals, respective.
Keywords: Mares